2007
DOI: 10.1007/s00726-007-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of antitumoural MGBG: the structural variable

Abstract: The present study aims at determining the structure-activity relationships (SAR's) ruling the biological function of MGBG (methylglyoxal bis(guanylhydrazone)), a competitive inhibitor of S-adenosyl-L-methionine decarboxylase displaying anticancer activity, involved in the biosynthesis of the naturally occurring polyamines spermidine and spermine. In order to properly understand its biochemical activity, MGBG's structural preferences at physiological conditions were ascertained, by quantum mechanical (DFT) calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…However, subsequent clinical investigations have shown that particular administration conditions strongly reduce MGBG's toxicity while preserving its antitumoural action (Von Hoff 1994). In order to establish the relationship between MGBG's structural preferences and its biological action-in particular, its transport mechanism(s), binding to macromolecular structures and MPT prevention-a conformational analysis in aqueous solution, as a function of pH, was carried out through theoretical methods (Marques et al 2008). A complete geometry optimisation was carried out, considering the molecule's different protonation states, with particular emphasis on the diprotonated form, which is the major species under physiological conditions (pK (MGBG) = 7.5 and 9.2).…”
Section: Biological Function Of Anticancer Methylglyoxal Bis(guanylhymentioning
confidence: 99%
“…However, subsequent clinical investigations have shown that particular administration conditions strongly reduce MGBG's toxicity while preserving its antitumoural action (Von Hoff 1994). In order to establish the relationship between MGBG's structural preferences and its biological action-in particular, its transport mechanism(s), binding to macromolecular structures and MPT prevention-a conformational analysis in aqueous solution, as a function of pH, was carried out through theoretical methods (Marques et al 2008). A complete geometry optimisation was carried out, considering the molecule's different protonation states, with particular emphasis on the diprotonated form, which is the major species under physiological conditions (pK (MGBG) = 7.5 and 9.2).…”
Section: Biological Function Of Anticancer Methylglyoxal Bis(guanylhymentioning
confidence: 99%
“…The data are expressed as a percentage of the control MTT reduction (100%), and represent the average±SD from one independent experiments carried out in duplicate (*p < 0.05; **p < 0.001 and # p < 0.0001). cultures of rat hepatocytes [20] as well as on a reported study on human histiocytic lymphoma that evidenced a decrease in protein synthesis after 20 to 25 h of exposure to the compound [21]. MGBG´s antiproliferative activity is suggested to be delayed due to conformational rearrangements undergone by the molecule at physiological conditions (since several species, with distinct activities, may coexist in the plasma).…”
Section: Resultsmentioning
confidence: 99%
“…MGBG´s cellular uptake is proposed to occur through the transport system of biogenic polyamines [20]. By inhibiting S-adenosylmethionine decarboxylase, it leads to a decrease of the spermidine and spermine intracellular concentration, consequently reducing in vitro cell growth and viability.…”
Section: Resultsmentioning
confidence: 99%
“…MGBG is another compound, which directly activates the mitochondrial pathway. MGBG produces reactive oxygen species, interacts with the polyamine metabolism and thereby impairs the mitochondrial function [137].…”
Section: Conventional Oncologic Therapiesmentioning
confidence: 99%